2016
DOI: 10.1152/jn.00708.2015
|View full text |Cite
|
Sign up to set email alerts
|

Frontal and motor cortex contributions to response inhibition: evidence from electrocorticography

Abstract: Changes in the environment require rapid modification or inhibition of ongoing behavior. We used the stop-signal paradigm and intracranial recordings to investigate response preparation, inhibition, and monitoring of task-relevant information. Electrocorticographic data were recorded in eight patients with electrodes covering frontal, temporal, and parietal cortex, and time-frequency analysis was used to examine power differences in the beta (13-30 Hz) and high-gamma bands (60-180 Hz). Over motor cortex, beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 66 publications
3
49
0
Order By: Relevance
“…Several attempts have been made to link specific electrophysiological signatures to inhibitory mechanisms (see [10, 140] for reviews). The initiation of voluntary movements is associated with desynchronization of activity in the beta frequency band (13–30 Hz) in electrocorticography (ECoG) and scalp electroencephalography (EEG) recordings over motor cortex [141143].…”
Section: Multiple Forms Of Motor Inhibition During Human Behaviormentioning
confidence: 99%
“…Several attempts have been made to link specific electrophysiological signatures to inhibitory mechanisms (see [10, 140] for reviews). The initiation of voluntary movements is associated with desynchronization of activity in the beta frequency band (13–30 Hz) in electrocorticography (ECoG) and scalp electroencephalography (EEG) recordings over motor cortex [141143].…”
Section: Multiple Forms Of Motor Inhibition During Human Behaviormentioning
confidence: 99%
“…Neither predicted deviants nor standards elicited any meaningful PFC activation, while sensory areas did not distinguish between predicted and unpredicted deviants. Notably, the PFC became active when unexpected errors were detected [32]. This raises the question how the PFC encodes predicted task contexts and other behaviorally relevant rules.…”
Section: Oscillatory Mechanisms Guiding Behavior and Cognitionmentioning
confidence: 99%
“…Moreover, electrocorticography (ECoG) studies, which record electroencephalography (EEG) signals directly from the surface of the brain, have shown that one electrophysiological signature of stopping is a power increase in the rIFC for successful vs. failed stop trials, before the time of stopping elapses i.e. Stop Signal Reaction Time, SSRT (Swann, et al, 2009; Wessel, et al, 2013) [but see Fonken et al (2016)]. These power increases occurred in the beta band, as do power increases in the basal ganglia during stopping (e.g.…”
Section: Introductionmentioning
confidence: 99%